Putusnya Perkawinan Karena Li’an Dalam Pandangan Maqashid Syariah - Rima Junita Putri; Yohana Dwi Putri; Lili Marzila; Wismanto Wismanto; Rafifah Qanita; Nailah assahira (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The li'an incident occurred because a husband accused his wife of adultery and did not acknowledge the child she gave birth to. Discussing this issue is very important, especially in the current situation where technological advances and times require firm and clear legal regulations to prevent li'an events in the Muslim family environment. Because Li'an attaches importance to the integrity and continuity of the relationship The marriage is forever. The breakup of marriage carried out by li'an is one form of marriage fasakhnya, which means the breakup of the marriage forever and is not allowed to return or reconcile. Separately, because of li'an, the child's bloodline has been cut off, and the child was taken from his.